A Short-Day Photoperiod Delays the Timing of Puberty in Female Mice via Changes in the Kisspeptin System - Bohlen, Tabata Mariz; Silveira, Marina Augusto; Buonfiglio, Daniella do Carmo; Ferreira-Neto, Hildebrando Candido; Cipolla-Neto, José; Donato, Jose; Frazao, Renata (Frontiers in Endocrinology, 2018)
The reproduction of seasonal breeders is modulated by exposure to light in an interval of 24 hours defined as photoperiod. The interruption of reproductive functions in seasonally breeding rodents is accompanied by the suppression of the Kiss1 gene expression, which is known to be essential for reproduction. In non-seasonal male rodents, such as rats and mice, short-day photoperiod (SP) conditions or exogenous melatonin treatment also have anti-gonadotropic effects; however, whether photoperiod is able to modulate the puberty onset or Kiss1 gene expression in mice is unknown. In the present study, we investigated whether photoperiodism influences the sexual maturation of female mice via changes in the kisspeptin system. We observed that SP condition delayed the timing of puberty in female mice, decreased the hypothalamic expression of genes related to the reproductive axis and reduced the number of Kiss1-expressing neurons in the rostral hypothalamus. However, SP also reduced the body weight gain during development and affected the expression of neuropeptides involved in the energy balance regulation. When body weight was recovered via a reduction in litter size, the timing of puberty in mice born and raised in SP was advanced and the effects in hypothalamic mRNA expression were reverted. These results suggest that the SP delays the timing of puberty in female mice via changes in the kisspeptin system, although the effects on hypothalamic-pituitary-gonadal axis are likely secondary to changes in body weight gain.